Effects of physical and chemical pretreatments on drying and quality properties of blackberry (Rubus spp.) in hot air dryer - Mohammad Kaveh (Food Science & Nutrition, 2020)
Abstract This research examines the impact of various pretreatments on effective moisture diffusivity coefficient (Deff), activation energy (Ea), specific energy consumption (SEC), color, and shrinkage of blackberry (Rubus spp.). Hot air drying experiments were conducted under three different temperatures (50, 60, and 70°C) and four pretreatments, including thermal pretreatment by hot water blanching at 70, 80, and 90°C, pulse pretreatment with microwave having power of 90, 180, and 360 W, chemical pretreatment using ascorbic acid (1% in distilled water), and mechanical pretreatment using ultrasonic vibration with working frequency of 28 ± 5% kHz for 15, 30, and 45 min. The results show that the highest Deff value, which was 1.00 × 10–8 m2/s, could be achieved by using a microwave pretreatment with power and drying temperature of 360 W and 70°C͘, respectively. Moreover, the lowest Deff value obtained from this similar pretreatment condition was 3.10 × 10–9 m2/s at a drying temperature of 50°C, while Ea ranged from 13.61 to 26.02 kJ/mol. The highest and lowest SECs were 269.91 kW hr/kg for the control sample and 75.63 kW hr/kg for the microwave pretreatment, respectively. Furthermore, the largest color change and shrinkage were detected in ascorbic acid pretreatment and control sample, respectively.